How do students adapt to Islamic boarding school? An exploration of factors that affect school well-being - Pulungan, Muhammad Syukri; Rizal, Fauzi; Fajarini, Ulfah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The compulsory boarding program at State Islamic University (UIN) of Syekh Ali Hasan Ahmad Addary Padangsidimpuan is designed to foster academic discipline, religious character, and social responsibility. The transition to a communal environment with strict rules, the rhythm of congregational worship, and structured learning targets requires each student to adapt in ways that are not uniform. This research aimed to understand in depth how first-year students interpret the process of adjustment to dormitory life and how this process is related to their school well-being. Using Interpretive Phenomenological Analysis (IPA), we conducted semi-structured interviews with eleven students and one dormitory supervisor, supported by observational data on daily dormitory routines. Thematic analysis yielded five interdependent dimensions: Having (material sufficiency and perceived institutional care), Loving (relational support and sense of belonging), Being (structured growth and self-regulation), Health (physical-mental balance), and Religiosity (faith-based meaning-making). Participants often reframe environmental tensions such as insufficient water, overcrowding, or burnout through spiritual resilience, making religiosity an important interpretive filter that links resource constraints to emotional stability and moral development. This integration extends Konu & Rimpelä's (2002) conventional model of SWB by placing religiosity as a core mediator in the setting of religion-based education. These findings informed a dormitory management strategy to integrate basic services, inclusive peer support, reflective scheduling, psychosocial counseling, and spiritual health to encourage sustainable adaptation and holistic student well-being.